Sociology of diagnosis - McGann, P. J.; Hutson, David J.; Rothman, Barbara Katz. (Bingley, U.K. : Emerald, 2011)
This is the only book to provide a comprehensive introduction to the sociology of diagnosis through original theoretical and empirical work by established and emerging scholars and, as such, it is poised to become a touchstone volume. Sixteen articles are presented across four sections. 'Power and the Politics of Diagnosis' explores diagnosis as a process of definition that includes: labeling dynamics between 'diagnoser' and diagnosed; boundary struggles between diverse constituents - both among medical practitioners and between medical authorities and others (such as lay persons, legal, religious, and/or governmental agents); and, the symbolic and material interests behind contested diagnoses. 'Identity, Experience, and Action' analyzes the impact of diagnosis on individual identity and illness experience, diagnosis as a basis for collective identity, and social action in relation to diagnoses. 'Diagnosis and Social Control' considers the role of diagnosis in norm enforcement and the production of moral boundaries and social standards, and diagnosis in relation to medicalization. 'Nosological Dynamics' explores diagnoses as socio-politico entities embedded in social relations.
Sociology of diagnosis : a preliminary review / Annemarie Jutel -- Diagnosis and medicalization / Karl Bryant -- Defining social illness in a diagnostic world : trauma and the cultural logic of posttraumatic stress disorder / Thomas DeGloma -- Resisting American psychiatry : French opposition to DSM-III, biological reductionism, and the pharmaceutical ethos / Manuel Vallée -- Labeling, looping, and social control : contextualizing diagnosis in mental health care / Kerry Dobransky -- From talk to action : mapping the diagnostic process in psychiatry / Rebecca Godderis -- 'DSD is a perfectly fine term' : reasserting medical authority through a shift in intersex terminology / Georgiann Davis -- Resisting pathology : GID and the contested terrain of diagnosis in the transgender rights movement / Mary C. Burke -- Navigating professional knowledges : lay techniques for the management of conflictual diagnosis in an AD/HD support group / Paul C. Fuller -- The vanishing diagnosis of Asperger's disorder / Jennifer S. Singh -- Hidden diagnosis : attention deficit hyperactivity disorder from a child's perspective / Elizabeth H. Bringewatt -- Sick but legitimate? : gender identity disorder and a new gender identity category in Japan / Satoko Itani -- Diagnosing the criminal addict : biochemistry in the service of the state / Sarah Whetstone, Teresa Gowan -- Troubling diagnoses / PJ McGann.
Mode of access: World Wide Web.
Print version record
Keywords: Social Science -- Sociology -- General; Medical -- General; Medical -- Epidemiology; Medical sociology; Epidemiology & medical statistics; Social medicine; Diagnosis -- Social aspects